The Armenian Theme in Stanislav Rassadin’s Critical Legacy - Janpoladyan, Magda (Bulletin of Yerevan University H: Russian Philology, 2022)
The article analyzes and evaluates the works of prominent Russian critic Stanislav Rassadin (1935-2012) dedicated to Armenian literature, particularly medieval and modern poets, as well as Russian poets, who touched upon the theme of Armenia. The peculiarities of the author's analytical thought are revealed in the article, his observations and conclusions are emphasized (especially about Narekatsi և Kuchak). The articles about Rassadin, S. Kaputikyan, H. Sahyan, P. Sevak are singled out, as well as the theme of Armenia in Lipkin's poetry. Appreciating and emphasizing the value of Rassadin's analysis, at the same time the author of the article expresses his own opinion, sometimes arguing with him.
Keywords: Rassadin; Narekatsi; Kuchak; contemporary poets; peculiarities of analysis; the value of critical judgments